2003
DOI: 10.1007/s10265-003-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of betaine aldehyde dehydrogenase from Avena sativa

Abstract: Betaine aldehyde dehydrogenase (BADH; EC 1.2.1.8) is the enzyme that catalyzes the second step in the synthesis of the osmoprotectant, glycine betaine. NADdependent BADH was purified from Avena sativa shoots by DEAE Sephacel, hydroxyapatite, 5 ¢ -AMP Sepharose 4B, Mono Q and TSK-GEL column chromatographies to homogeneity by the criterion of native PAGE, and the properties of BADH were compared with those of aminoaldehyde dehydrogenase purified to homogeneity from A. sativa . The molecular mass estimated by bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…The exception was the A441F mutant, which showed lower k cat / K m values for both BAL and APAL than the wild-type and the other mutant enzymes, which suggest important structural alterations in the active site of this mutant. The catalytic efficiencies ( k cat / K m ) for APAL of the wild-type and mutants So BADH enzymes are higher than that for BAL (Table 2), as it has been found with other A441- or C441-type ALDH10 isoenzymes that in addition to the AMADH activity exhibit BADH activity [7,9,20]. Another difference between the kinetics with BAL and APAL is that APAL produced a small but clear substrate inhibition in the wild-type and mutant So BADHs, while this inhibition was not observed in the saturation kinetics with BAL in the concentration range studied.…”
Section: Resultsmentioning
confidence: 75%
“…The exception was the A441F mutant, which showed lower k cat / K m values for both BAL and APAL than the wild-type and the other mutant enzymes, which suggest important structural alterations in the active site of this mutant. The catalytic efficiencies ( k cat / K m ) for APAL of the wild-type and mutants So BADH enzymes are higher than that for BAL (Table 2), as it has been found with other A441- or C441-type ALDH10 isoenzymes that in addition to the AMADH activity exhibit BADH activity [7,9,20]. Another difference between the kinetics with BAL and APAL is that APAL produced a small but clear substrate inhibition in the wild-type and mutant So BADHs, while this inhibition was not observed in the saturation kinetics with BAL in the concentration range studied.…”
Section: Resultsmentioning
confidence: 75%
“…The concentration of 2-acetyl-1-pyrroline in rice is influenced by the environment, and has been reported to be higher in plants subjected to water stress (Yoshihashi et al ., 2004). BAD has been associated with stress tolerance in plants (Nakamura et al ., 2001;Li et al ., 2003;Livingstone et al ., 2003). A gene that encodes BAD from a halophyte ( Suaeda liaatungenis ) improved salt tolerance when expressed in tobacco (Li et al ., 2003).…”
Section: Resultsmentioning
confidence: 99%
“…142 However, recent studies have shown that BADH2 is capable of metabolising a range of substrates including -aminoaldehydes, often more efficiently than betaine aldehyde. 139,143,144 When expressed in E. coli, BADH2 shows a greater affinity for GABald than for betaine aldehyde and it is capable of oxidising GABald to GABA. 120,139 Thus, BADH2 participates in the pathway of GABA synthesis by oxidising GABald/Δ1-pyrroline.…”
Section: Biochemical Basis Of 2ap Biosynthesismentioning
confidence: 99%